Longitudinal comparison of treat-to-target states and clinical outcomes in patients with late-onset versus early-onset systemic lupus erythematosus - Worawit Louthrenoo; Alberta Hoi; Vera Golder; Yi-Hsing Chen; Jiacai Cho; Aisha Lateef; Laniyati Hamijoyo; Yeong-Jian Jan Wu; Sandra V. Navarra; Leonid Zamora; Zhanguo Li; Sargunan Sockalingam; et al. (The Journal of Rheumatology, 2026)
Objective We compared demographic and clinical characteristics between patients with late-onset (LO) and early-onset (EO) systemic lupus erythematosus (SLE) and examined their longitudinal associations with treatment targets and long-term outcomes, irreversible organ damage accrual and health-related quality of life (HRQoL). Methods We analyzed prospectively collected data from patients enrolled in the Asia Pacific Lupus Collaboration cohort. Patients diagnosed with SLE at age >50 years were classified as LO-SLE and compared with those diagnosed at age ≤50 years (EO-SLE). Longitudinal associations with treatment targets (LLDAS and DORIS remission), organ damage accrual (SLICC/ACR Damage Index), and HRQoL (SF36v2 physical and mental component summary (PCS and MCS) scores) were examined using multivariable multilevel logistic, recurrent-event survival, and linear mixed-effects models, respectively. Disease activity, flares, medication exposure, and other clinical characteristics were also compared between groups. Results Among 3,917 patients studied, 346 (8.8%) had LO-SLE. Compared with EO-SLE, patients with LO-SLE had lower disease activity, lower glucocorticoid and immunosuppressant exposure, and higher attainment of treatment targets; LO-SLE was associated with higher odds of attaining LLDAS (OR: 2.33 (1.66, 3.28)) and DORIS remission (OR: 2.22 (1.45, 3.38)). However, they were at a greater risk of damage accrual (HR:1.82 (1.50, 2.21)) and lower PCS scores, meaning poorer physical health (regression coefficient (RC) = -3.63 (-4.58, -2.68)) but not MCS (RC= 0.68 (-.50, 1.86)). Conclusion Despite higher attainment of treatment targets, patients with LO-SLE experienced greater damage accrual and poorer physical health, suggesting that disease activity targets alone may not fully capture outcome risk in LO-SLE.